2004
DOI: 10.1194/jlr.m400220-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein retains function when reconstituted into a sphingolipid- and cholesterol-rich environment

Abstract: P-glycoprotein (P-gp) appears to be associated within specialized raftlike membrane microdomains. The activity of P-gp is sensitive to its lipid environment, and a functional association in raft microdomains will require that P-gp retains activity in the microenvironment. Purified hamster P-gp was reconstituted in liposomes comprising sphingomyelin and cholesterol, both highly enriched in membrane microdomains and known to impart a liquid-ordered phase to bilayers. The activity of P-gp was compared with that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 55 publications
3
58
1
Order By: Relevance
“…The homodimeric ABCG2 protein was even more sensitive to detergents than ABCB1, and the addition of extra lipids at the solubilization step was indispensable for maintaining activity (Telbisz et al, 2014). Reconstitution studies showed that purified ABCB1 can be functional in several types of liposomes, composed of different phosphatidylcholine (PC) and phosphatidylethanolamine (PE) mixtures, and the addition of cholesterol is not required for full activity (Bucher et al, 2007;Doige et al, 1993;Kimura, Kioka, et al, 2007;Modok, Heyward, & Callaghan, 2004). ABCB1 was active even in pure DMPE or DPPE liposomes, but the application of PC:PE mixtures increased activity and unsaturated lipids also had an activating role .…”
Section: P0230mentioning
confidence: 99%
“…The homodimeric ABCG2 protein was even more sensitive to detergents than ABCB1, and the addition of extra lipids at the solubilization step was indispensable for maintaining activity (Telbisz et al, 2014). Reconstitution studies showed that purified ABCB1 can be functional in several types of liposomes, composed of different phosphatidylcholine (PC) and phosphatidylethanolamine (PE) mixtures, and the addition of cholesterol is not required for full activity (Bucher et al, 2007;Doige et al, 1993;Kimura, Kioka, et al, 2007;Modok, Heyward, & Callaghan, 2004). ABCB1 was active even in pure DMPE or DPPE liposomes, but the application of PC:PE mixtures increased activity and unsaturated lipids also had an activating role .…”
Section: P0230mentioning
confidence: 99%
“…S6 A and B). Small increases in K cat /K m , of the order of fourfold on reconstitution are a common feature of many ABC transporters (29)(30)(31). The basal ATPase activity is inhibited by vanadate (Fig.…”
Section: Structure Abcb10 In Complex With Nucleotide Analogs and Withoutmentioning
confidence: 99%
“…The lipid environment influences the ATPase activity of P-glycoprotein. [51][52][53][54][55] Modok et al 53) showed that P-glycoprotein retains function in liquid-ordered cholesterol and sphingolipid model membranes. Gayet et al 55) showed that cholesterol increases with the level of chemoresistance in human CEM acute lymphoblastic leukemia.…”
Section: Metabolic Inhibitors As a Tool To Study Sphingolipid Functionsmentioning
confidence: 99%